Rational Functionalization Towards Redox‐Active TEMPO Stable Free‐Radical‐Hydrochar Composites. Issue 9 (31st March 2021) - Patrinoiu, Greta; Calderon‐Moreno, Jose M.; Somacescu, Simona; Musuc, Adina M.; Spataru, Tanta; Ionita, Petre; Carp, Oana
Abstract: Although both stable free organic radicals and biomass‐derived hydrochars have emerged as appealing, green, multifunctional materials, their association has not been explored. In this study, strength is found to lie in their union, which primarily leads to stable redox‐active free‐radical‐hydrochar composites that can generate unexpected opportunities for the development of advanced metal‐free sustainable materials. The composites are obtained by a straightforward green one‐pot hydrothermal procedure. The loading of stable free radicals of nitroxide type and their localization is engineered by the nature of the carbohydrate and the reaction status; vigorous reaction parameters promote faster nucleation and growth kinetics of the hydrochar products, leading to a covalent immobilization of redox species on the surface of the carbonaceous microspherical aggregates. The nitroxide free‐radical‐hydrochar materials demonstrate enhancements in terms of both electrocatalytic activity and capacitive features. Abstract : Berry necessary : Redox‐active stable free radical‐biohydrochar composites are formulated by using a simple, green, one‐pot hydrothermal approach, whereby radical species are integrated onto/into a simultaneously generated hydrothermal carbonaceous matrix. The blackberry‐like materials demonstrate enhancements in both electrocatalytic activity and capacitive features.